Short communication: Heat stress does not affect induced luteolysis in Holstein cows - Mogollón, H. D.G. [UNESP]; Ferrazza, R. A. [UNESP]; Vallejo, V. H. [UNESP]; Destro, F. C. [UNESP]; Ochoa, J. C. [UNESP]; Nogueira, C. [UNESP]; Carvalho, R. F. [UNESP]; Moraes, L. N. [UNESP]; Rizzoto, G.; Sartori, R.; Wiltbank, M. C.; Ferreira, J. C.P. [UNESP] (American Dairy Science Association, 2020)
Heat stress (HS) has deleterious effects on bovine reproduction, including prolongation of the luteal phase in Holstein cows, perhaps due to compromised luteolysis. The objective was to characterize effects of HS on luteolytic responses of nonlactating Holstein cows given 25 or 12.5 mg of PGF2α on d 7 of the estrous cycle. Cows were randomly distributed into 2 environments: thermoneutral (n = 12; 25°C) or HS (n = 12; 36°C). In each environment, cows were treated with 2 mL of saline, 25 or 12.5 mg of PGF2α (n = 4 cows per group). The HS environment induced a significant increase in rectal temperature and respiratory rate compared with the thermoneutral environment. Heat stress did not have significant effects on luteolytic responses or circulating progesterone concentrations. Rapid and complete luteolysis occurred in all cows given 25 mg of PGF2α and in 4 of 8 cows given 12.5 mg; the other 4 cows given 12.5 mg had partial luteolysis, with circulating progesterone concentrations initially suppressed, but subsequently rebounding. Therefore, we conclude that HS does not change corpus luteum sensitivity to PGF2α.
Keywords: cattle; corpus luteum; progesterone; prostaglandin